Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2015)
In Jan Ch Karlsson’s debate article in this issue he urges all of us to reveal “factoids”. Factoids are statements that are repeated so often that they appear as facts even though they are not, and he provides us with some examples of common factoids concerning working life. This issue presents seven articles dealing with different subjects within working life research, all providing us with new knowledge and insights on working life conditions with potential to reveal factoids. The articles also provide us with knowledge that can be used in practical contexts in working life. In addition to these seven articles the issue contains two comprehensive book reviews, books that contribute to the conceptual development of working life research, namely a review of Nancy Harding’s book “On Being at Work. The Social Construction of the Employee”, and Steven Peter Vallas’ book “Work” (...)